A perspective on the Langmuir adsorption model applied to molecular liquid crystals containing ions and nanoparticles - Garbovskiy, Yuriy (Frontiers in Soft Matter, 2022)
Electrical properties of molecular liquid crystals doped with nanomaterials have been extensively studied over the past two decades. In general, nanoparticles in liquid crystals can play a dual role acting as either ion capturing agents or ion generating objects. An interplay between ions and nanomaterials in liquid crystals can result in a great variety of nontrivial ionic effects. This perspective discusses the Langmuir adsorption model applied to describe ionic phenomena in molecular liquid crystals doped with nanoparticles. The applicability and limitations of this model are emphasized. Within a range of its applicability, the Langmuir adsorption model can be used to obtain a wealth of information about nanoparticle-induced ionic effects in molecular liquid crystals. In addition, this model also offers important improvements to standard experimental procedures for evaluation of electrical properties of advanced liquid crystal materials.